2011
DOI: 10.1161/strokeaha.111.618306
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transient Receptor Potential Vanilloid 1 by Dietary Capsaicin Delays the Onset of Stroke in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Background and Purpose-Previous studies show that endothelial nitric oxide synthase (eNOS) plays a prominent role in maintaining cerebral blood flow and preventing stroke. Capsaicin in hot pepper can increase the phosphorylation of eNOS in endothelial cells. We test the hypothesis that chronic dietary capsaicin can prevent stroke through activation of cerebrovascular transient receptor potential vanilloid 1 (TRPV1) channels in stroke-prone spontaneously hypertensive rats (SHRsp). Methods-SHRsp were fed dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Several studies have shown that capsaicin and its target, TRPV1, are implicated in hypertension. 20 The renal sensory nerves that express TRPV1, and various neuropeptides, including potent vasodilators, are released on TRPV1 activation. 21 Rats develop salt-sensitive hypertension after TRPV1 sensory degeneration by capsaicin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that capsaicin and its target, TRPV1, are implicated in hypertension. 20 The renal sensory nerves that express TRPV1, and various neuropeptides, including potent vasodilators, are released on TRPV1 activation. 21 Rats develop salt-sensitive hypertension after TRPV1 sensory degeneration by capsaicin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some arteries were incubated with the nitric oxide synthase (NOS) inhibitor L-NAME (100 μmol/L, 30 minutes) before measuring EDR. Endothelium-independent relaxation in response to nitroglycerin (NTG) was measured in basilar rings [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…The endogenous cannabinoid signaling system or endocannabinoid (eCB) system, which involves arachidonic Cannabinoid System (49)(50)(51)(52)(53) WIN55212-2 CB1 agonist at POAH (57,58) Reduced excitotoxicity via glutamate release (50) Titrated 1-10 mg/kg (50) Dose dependent: (50,52) Sprague-Dawley rats (52) 1 mg/kg 1 mg/kg  0 °C (53) Wistar rats (53) 9 mg/kg with active rewarming 2.5 mg/kg  -2.5 °C (59,60) Remyelination through oligodendrocyte proliferation 5 mg/kg  -3.4 °C 10 mg/kg  -3.4 °C (52) 1 mg/kg  0 °C (52) Reduced inflammation and microglia activation (61) Reduced BBB disruption (54) HU-210 (71)(72)(73) Capsaicin Effects through peripheral nerves and POAH (71) Phosphorylation of eNOS (72) ↓ Blood pressure (72) 0.02% standard chow (72) Stroke-prone spontaneously hypertensive rats (73) 0.3 mg/kg (73) Dogs (76) Anti-shivering thermoregulatory effects ↓ Heart rate (73) Transient ↓ blood pressure and ↓ Heart rate (75) Lead to neuronal apoptosis (74) DHC …”
Section: Cannabinoid Systemmentioning
confidence: 99%
“…74 Capsaicin (0.02% added to standard chow) has been shown to have protective effects against stroke via increased phosphorylation of endothelial nitric oxide synthase (eNOS) in stroke-prone spontaneously hypertensive rats. 75 However, studies have shown capsaicin (5-20 μg/kg) to have cardiovascular depressive effects such as hypotension and bradycardia in dogs. 76 A recent study has determined that the above effect may be due to impurities present in the administered capsaicin, as pure trans-capsaicin (0.3 mg/kg) only resulted in transient tachycardia and hypertension.…”
Section: Unknownmentioning
confidence: 99%